2000
DOI: 10.1111/j.1530-0277.2000.tb04613.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol on Brain Metallothionein in Transgenic Mice

Abstract: Acute or chronic ethanol administration can cause generation of oxygen free radical and oxidative stress to the brain. The generation of free radicals is thought to be one of the causes of cell injury after ethanol administration. The mechanism of induction of MT in brain after oral ethanol administration may be associated with oxidative stress caused by ethanol or its metabolites, and can be considered as a protective mechanism against ethanol toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…This elevation is seen in all four strains of mice (A/J, BALB/cJ, C57BL/6J, and DBA/2J). It follows reports by Suzuki and Cherian (2000), who noted an increase in brain MTs after ethanol treatment in C57BL/6J mice. This response may be activated through the ARE, seven metal regulatory elements (MREs), and/or other partially characterized regulatory features of the MT-II promoter (Andrews, 2000).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This elevation is seen in all four strains of mice (A/J, BALB/cJ, C57BL/6J, and DBA/2J). It follows reports by Suzuki and Cherian (2000), who noted an increase in brain MTs after ethanol treatment in C57BL/6J mice. This response may be activated through the ARE, seven metal regulatory elements (MREs), and/or other partially characterized regulatory features of the MT-II promoter (Andrews, 2000).…”
Section: Discussionsupporting
confidence: 79%
“…In addition to liver studies, research has shown the level of MT to be elevated in the brain of C57BL/6J mice after oral ethanol administration (Suzuki Cherian, 2000), and suggests that MT-I and MT-II help the brain and central nervous system cope with injury and neurotoxicity (Asanuma et al, 2002;Giralt et al, 2002;Hidalgo et al, 2001). Such results are consistent with the suggestion that the increase of MTs in the brain after ethanol exposure may offer protection against free radicals through their antioxidant properties and/or ability to bind and regulate cellular concentrations of zinc and copper.…”
mentioning
confidence: 99%
“…Several MT isoforms such as Cg‐MT2 have been described in C. gigas and have been shown to be inducible by metallic stress [56]. Metallothioneins also have diverse physiological functions including protection against oxidants [57]. Murphy et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to environmental stresses, ethanol reduces growth and immunity (Olfati, Mojtahedin, Sadeghi, Akbari, & Martínez‐Pastor, ) and disturbs oxidant and antioxidant balance (Habibian, Ghazi, Moeini, & Abdolmohammadi, ). Ethanol is oxidized into acetaldehyde with simultaneous breakdown of H 2 O 2 and produces acetaldehyde and free radicals (Suzuki & Cherian, ). Ethanol can induce oxidative stress, and it can be used as a model for inducing stress in broiler chicks.…”
Section: Introductionmentioning
confidence: 99%